Disintegrant properties of native and modified polymers in metronidazole tablet formulations (2014)
Natural polymers may be modified in order to improve desired properties in tablet formulations. Granule incorporation techniques have different effects on the disintegrant properties of tablets. Disintegrant properties of two new plant polymers, extracted from Pigeon pea (Cajanus cajan) and Khaya senegalensis tree, were investigated in metronidazole tablet formulations. Native and microwave irradiated forms of the starch and gum were incorporated into the tablet formulations using a 3-factor general full factorial design. Type of disintegrants (X1) was at two levels (Starch or Gum), effect of modification (X2) was also investigated at two levels (Native or Irradiated), while the mode of incorporation (X3) of the disintegrants was at three levels (Intragranular (IG), Extragranular (EG) or Intra-extragranular (IG/EG). Sodium starch glycolate was the standard. Tablets were evaluated for disintegration, dissolution and physical qualities using British Pharmacopoeia methods. The native and modified gum showed higher hydration capacity than the starches. The rank order of the disintegrant properties of the polymers was MG (modified gum)>NG (native gum)>MS (modified starch)>NS (native starch) (p<0.05). The crushing strength for tablets from both native and modified polymers was similar but differs with the mode of incorporation. In starch, the rank orders were IG/EG > IG > EG; and EG > IG/EG > IG for the gums. However, IG/EG incorporation of native and modified starches and gums gave a longer t80 (time taken for 80% of the drug to dissolve) than both IG and EG (p<0.05). The effect of the variables on the disintegrant properties of the polymers was in the order: X3 > X1 > X2 and the effect on t80 was X1 > X3 > X2. The gums and starches were better disintegrants than sodium starch glycolate, with the gums exhibiting better properties than the starches. Microwave irradiation had no significant effect on the disintegrant properties of both polymers but increased the crushing strength of the tablets. Intragranular incorporation proved to be the best method for optimum disintegrant property.